Tasas de inactividad en Argentina: Un estudio de datos composicionales - José Luis Iparraguirre D'Elia; Gerardo Roozen (Colegio de Economistas de A Coru\~na, 2009)
– The aim of this project is to apply a statistical analysis of compositional data in order to study the inactivity rate in the economy of Argentina. We try to confirm the hypothesis of allometric effects on overall levels of economic inactivity per big urban conglomerate and their features according to the different causes of inactivity. In other words, whether the percentage of inactives due to various reasons of inactivity is related to the inactivity rate per urban conglomerate. Allometric effects have been found in regional studies of inactivity in the United Kingdom. According to these, some causes of inactivity, such as incapacity, are strongly related to the overall levels of inactivity per region. However, results from May 2003 allow us to reject the hypothesis that inactivity components per urban conglomerate are directly related to inactivity rates.
Keywords: 330